Surgical management of gigantiform osteoma of angle causing facial deformity - Anehosur, Venkatesh; Kotian, Divya; Kumar, Niranjan (International Surgery Journal, 2022)
Osteoma is a rare, benign lesion wherein deposition of newly formed bone results in a tumor mass. Variants of osteomas can develop either as a peripheral mass arising from the periosteum or a central mass arising from the endosteum. Peripheral ones are usually asymptomatic and larger lesions primarily cause facial asymmetry. Central osteoma, in most cases results in cortical expansion and root displacement in some. Central osteomas pose a diagnostic dilemma and need to be discriminated from other similar lesions such as condensing osteitis, odontoma, ossifying fibroma, osteoblastoma. Isolated single osteomas are usually non-syndromic whereas, multiple osteomas are hallmark features of Gardner syndrome. Craniofacial bones such as paranasal sinuses and jawbones are frequently affected, although rare cases in other bones and soft tissues have been reported. This is a presentation of osteoma in the rare angle of mandible region in a young patient which was managed by intraoral approach.